Experimental determination of the impact energy of horse kicks. (July 2020) - Benthien, Jan T.; Ohlmeyer, Martin; Gäckler, Susanne; Krause, Andreas; Al Samarraie, Ahmed
Abstract : Kicking is a natural behaviour of horses, but it can become problematic if stall components are hit and do not withstand the impact load. Injuries may occur due to material failure or hoof entrapment. In Germany, while the Animal Protection Law is intended to prevent such incidents, neither the law nor the corresponding interpretation aid indicates how this requirement should be fulfilled. This paper gives an overview of the methods of determining horse kick energy and presents results of own kick energy measurements. The outcome of a re-evaluation of literature data is presented and two attempts to roughly estimate the expected kick load are introduced. The developed measuring device consists of a steel-made framework, mechanical energy sensors, and an impact panel. Its verification was carried out by loading with impacts of defined energy applied by a pendulum impact machine. The measurement of kick energy was taken at a stud farm in the context of heat detection by observing the response of a mare to the presence of a stallion, whereby the kicks of the stallion were measured. With regard to the kick-resistance and entrapment-safety calculation, a representative value of 71 J was calculated and using a safety factor of 1.5 this gives a design value of 106 J. The presented results and the theoretical background of kick energy measurements described should in the future form the basis for the dimensioning of kick-resistant and entrapment-secure stall planks. Graphical abstract: Image 1 Highlights: Theory background of horse kick energy determination. Horse kick measurement applying specially designed dynamic energy sensors. Kick energy determined to 106 J (design value) for stall plank dimensioning. Result validation performed by application of various estimation approaches. Kick-resistant and entrapment-safety stall plank dimensioning now possible.